Protection of adipose-derived mesenchymal stromal cells during acute lung injury requires autophagy maintained by mTOR - Yue Hu; Jing Shao; Lanying Shen; Shengchao Wang; Kaiyan Xu; Jiayan Mao; Jian Shen; Wei Chen (Cell Death Discovery, 2022)
Abstract Previous studies suggest that mesenchymal stem cells may represent a promising cellular therapy for acute lung injury (ALI); however, the underlying relevant molecular mechanisms remain unclear. Adipose-derived mesenchymal stem cells (ADSCs) were isolated and characterized by alizarin red staining, oil red staining, and flow cytometry. Lung injury and inflammatory cell infiltration were determined using the Evans blue method, wet/dry weight ratio, and H&E staining. An ELISA was used to detect the concentrations of IFN-γ, IL-2, and TNF-α. Autophagy was detected with an mRFP-GFP-LC3 dual-fluorescence autophagy indicator system, Western blotting, and electron microscopy. We first demonstrated that ADSCs did alleviate the inflammatory responses and tissue damage in lipopolysaccharide (LPS)-induced ALI. Next, we further demonstrated in vivo that autophagy plays a key role in the maintenance of ADSC therapeutic efficacy. In vitro experiments demonstrated that ADSCs co-cultured with alveolar epithelial cells depend on autophagy for significant anti-inflammatory functions. Moreover, the mammalian target of rapamycin (mTOR) is a key regulator of autophagy. Taken together, our findings demonstrate that the effect of ADSC on ALI, especially on alveolar epithelial cells, is dependent on mTOR-mediated autophagy maintenance. The significance of our study for ALI therapy is discussed with respect to a more complete understanding of the therapeutic strategy paradigm.